2014
DOI: 10.1371/journal.pone.0088079
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction Model for Colorectal Cancer: National Health Insurance Corporation Study, Korea

Abstract: PurposeIncidence and mortality rates of colorectal cancer have been rapidly increasing in Korea during last few decades. Development of risk prediction models for colorectal cancer in Korean men and women is urgently needed to enhance its prevention and early detection.MethodsGender specific five-year risk prediction models were developed for overall colorectal cancer, proximal colon cancer, distal colon cancer, colon cancer and rectal cancer. The model was developed using data from a population of 846,559 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 25 publications
(33 reference statements)
2
48
0
Order By: Relevance
“…While an Iranian study showed that family history of cancer increased the risk of CRC (33), Weibull model did not detect any relation between risk of mortality and family history of CRC and this is similar to an Asian study which could not find any relation with survival of CRC and family history (34). Although in Iran there is evidence to support the screening of average risk individuals, including person with family history of colorectal cancer (35), it is still controversial and needs to more research on the Iranian population.…”
Section: Discussionsupporting
confidence: 72%
“…While an Iranian study showed that family history of cancer increased the risk of CRC (33), Weibull model did not detect any relation between risk of mortality and family history of CRC and this is similar to an Asian study which could not find any relation with survival of CRC and family history (34). Although in Iran there is evidence to support the screening of average risk individuals, including person with family history of colorectal cancer (35), it is still controversial and needs to more research on the Iranian population.…”
Section: Discussionsupporting
confidence: 72%
“…Socio-demographic characteristics of the study populations A majority of the risk prediction models have been developed in United States of America [18,22,33,38,39,42,44,45,48,49,50,51,53,54] followed by Korea [14,17,20,35]. Three models have been developed in China [16,23,36] and Japan [40] while, Netherlands [25,26], Germany [21], Taiwan [32,46] and United Kingdom [31,34] have developed two models each.…”
Section: Questionnairementioning
confidence: 99%
“…However, 11 models are specific for females [20,22,35,42,45,50] while 10 models are specific for males [20,22,35,45,48]. Although many models have not restricted application to a specific age limit, 11 models have been developed from populations aged 30 years and above [15,20,42,43,50], 10 from populations aged 50 years and above [18,25,26,45,51] and seven from populations aged 40 years and above [14,19,23,24,36,38,52]. In addition, one model has used a population above 20 years [35] while another, populations lower than 80 years [34].…”
Section: Questionnairementioning
confidence: 99%
See 2 more Smart Citations